In Vitro Cytotoxicity and in Vivo Antitumour Properties of Kenaf Seed Oil Towards Leukaemia - Foo, Jhi Biau (2011)
The current treatments for leukaemia such as chemotherapy and radiation therapy have prolonged the survival rate. However, the adverse effects of these treatments are difficult to handle. Thus, there is a need to seek for other remedies, such as the use of natural products. Natural products such as plants play an important role in the current cancer treatment. The advantage of using plant-derived anticancer agents is that the produced adverse effects are lesser as compared to the synthetic drugs. Kenaf (Hibiscus cannabinus) seed oil (KSO) is a rich source of bioactive phytochemicals with high anti-oxidative and cancer chemopreventive properties. Nevertheless, the anti-leukaemia properties of KSO have yet been investigated. This study investigated the anti-leukaemia properties of KSO in vitro and in vivo. KSO was extracted by supercritical carbon dioxide fluid extractor (SFE), and evaluated for cytotoxic properties on leukaemia (HL-60, WEHI-3B and K562) and normal (3T3) cells by MTT assay with concentrations ranging from 50 to 800 μg/ml for 72 hours. The morphological changes of KSO-treated leukaemia cells were observed under an inverted light microscope and a fluorescence microscope. The cell cycle profile of KSO-treated leukaemia cells was analysed by flow cytometry. For in vivo, acute toxicity and anti-leukaemia properties of KSO were determined. Male BALB/c mice were injected intraperitoneally with WEHI-3B cells and administered orally with KSO at the dose of 0.5, 1.0 and 1.5 g/kg for 14 days. Upon completion, the blood of the mice was examined for the expression of cell surface marker of T cell (CD3), B cell (CD19), monocyte and granulocyte (CD11b) by staining with anti-CD3-FITC, anti-CD19-PE and anti-CD11b-PE antibodies, respectively. The livers and spleens were isolated, weighed and photographed. The spleens were processed for histopathological analysis. The yield of KSO by SFE ranged from 11 to 13% (w/w). KSO was found to be cytotoxic towards all the leukaemia cells in a dose-dependent manner with no effects on 3T3 cells even at the highest concentration employed (800 μg/ml). Oil from SFE at 600 bar 40 ºC (KSO V600/40) was the most cytotoxic towards HL-60, WEHI-3B and K562 cells as compared to other extractions (KSO V600/60, KSO V600/80 and Soxhlet) with the 50% inhibition concentration (IC50) values of 178.78±10.52, 189.43±11.63 and 213.33±15.45 μg/ml, respectively. KSO V600/40-treated leukaemia cells exhibited typical characteristics of apoptosis such as cellular shrinkage, membrane blebbing, chromatin condensation and nuclear fragmentation. Cell cycle analysis revealed that KSO V600/40 at IC50 value induced G1 phase cell cycle arrest and significantly increased (p<0.05) the sub-G1 apoptotic population in the leukaemia cells. For in vivo, acute toxicity study revealed that KSO V600/40 did not cause any mortality in the healthy normal mice even at the highest dose (5.0 g/kg), suggesting that KSO is non-toxic by oral route. Treatment with KSO V600/40 at 1.0 and 1.5 g/kg increased the population of T cells, but decreased the population of immature monocytes and granulocytes in the blood of WEHI-3B injected BALB/c mice (WEHI-3B/BALB/c mice). Spleen and liver weight of WEHI-3B/BALB/c mice decreased after the treatment with KSO V600/40. Moreover, infiltration of leukaemic cells into the splenic red pulp reduced after the treatment, indicating that KSO V600/40 reduced the severity of leukaemia in WEHI-3B/BALB/c mice. In conclusion, KSO V600/40 showed cytotoxic effect via the induction of G1 phase cell cycle arrest and apoptosis in the leukaemia cells, and reduced the severity of leukaemia in WEHI-3B/BALB/c mice.